2022
DOI: 10.4103/jomfp.jomfp_115_21
|View full text |Cite
|
Sign up to set email alerts
|

Senescent Fibroblast in Oral Submucous Fibrosis Aids in Disease Progression and Malignant Transformation

Abstract: Aim: To study the role of senescent fibroblasts (SFs) and its secretory phenotypes promoting fibrosis and malignancy in oral submucous fibrosis (OSMF). Material Methods: A total of 20 cases of OSMF and 20 normal oral mucosal tissues were taken for the study. The tissue sections were stained for IHC-immunohistochemistry with senescent cell marker p16INK4a. The supernatant solution of the transport medium was studied for leached out senescent associated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Indeed, infection-induced senescence has been shown to involve toxins, viral capsids and flagella [ 67 , 68 , 69 , 70 , 71 ]. It should be noted that several studies have also demonstrated that bacterial factors such as Porphyromonas gingivalis lipopolysaccharide (LPS) can induce senescence in fibroblasts and dendritic cells, thereby contributing to periodontal disease-associated inflammation [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, infection-induced senescence has been shown to involve toxins, viral capsids and flagella [ 67 , 68 , 69 , 70 , 71 ]. It should be noted that several studies have also demonstrated that bacterial factors such as Porphyromonas gingivalis lipopolysaccharide (LPS) can induce senescence in fibroblasts and dendritic cells, thereby contributing to periodontal disease-associated inflammation [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%